Sea salt reactivity over the northwest Atlantic: an in-depth look using the airborne ACTIVATE dataset - E.-L. Edwards; Y. Choi; Y. Choi; E. C. Crosbie; E. C. Crosbie; J. P. DiGangi; G. S. Diskin; C. E. Robinson; C. E. Robinson; M. A. Shook; E. L. Winstead; E. L. Winstead; et al. (Atmospheric Chemistry and Physics, 2024)
Chloride (Cl−) displacement from sea salt particles is an extensively studied phenomenon with implications for human health, visibility, and the global radiation budget. Past works have investigated Cl− depletion over the northwest Atlantic (NWA); however, an updated, multi-seasonal, and geographically expanded account of sea salt reactivity over the region is needed. This study uses chemically resolved mass concentrations and meteorological data from the airborne Aerosol Cloud meTeorology Interactions oVer the western ATlantic Experiment (ACTIVATE) to quantify seasonal, spatial, and meteorological trends in Cl− depletion and to explore the importance of quantifying (1) non-sea salt sources of Na+ and (2) mass concentrations of lost Cl− (instead of relative amounts displaced). Lost Cl− mass concentrations are lowest in December–February and March, moderate around Bermuda in June, and highest in May (median losses of 0.04, 0.04, 0.66, and 1.76 µg m−3, respectively), with losses in May that are high enough to potentially accelerate tropospheric oxidation rates. Inorganic acidic species can account for all Cl− depletion in December–February, March, and June near Bermuda but none of the lost Cl− in May, suggesting that organic acids may be of importance for Cl− displacement in certain months. Contributions of dust to Na+ are not important seasonally but may cause relevant overestimates of lost Cl− in smoke and dust plumes. Higher percentages of Cl− depletion often do not correspond to larger mass concentrations of lost Cl−, so it is highly recommended to quantify the latter to place depletion reactions in context with their role in atmospheric oxidation and radiative forcing.